(untitled) (Ozone Therapy Global Journal, 2014)
Ozone (O3), an allotrope of the Oxygen (O2), is normally present in atmosphere and it preserves us from solar ultraviolet rays. It was used for first time like antiseptic during First World War. In ’30 years Payr 82 extends its use to other diseases too. The same period it ascends the use of ozone for drinking in important citis, like Zurich, Marseilles, Singapore, Florence, Moscow, Konstanz. It has been shown ozone has an immunostimulatory effect at low concentration (20-35 μg/ml), while it is immunosoppressive if it is used at high concentration (45-65 μg/ml) 60. In 2002 Marx and Bardi 14 have demonstrated like in nature IgG execised a bactericidal action releasing O3.